2021
DOI: 10.3390/plants10112238
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Identification, Genomic Organization, and Characterization of Potassium Transport-Related Genes in Cajanus cajan and Their Role in Abiotic Stress

Abstract: Potassium is the most important and abundant inorganic cation in plants and it can comprise up to 10% of a plant’s dry weight. Plants possess complex systems of transporters and channels for the transport of K+ from soil to numerous parts of plants. Cajanus cajan is cultivated in different regions of the world as an economical source of carbohydrates, fiber, proteins, and fodder for animals. In the current study, 39 K+ transport genes were identified in C. cajan, including 25 K+ transporters (17 carrier-like K… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 66 publications
3
8
0
Order By: Relevance
“…Some transporters, namely HvHAK1 , HvAKT2 , OsHAK1 , and OsHAK5 , have been shown to be involved in the uptake of K + in the roots [ 53 , 54 ]. Expression analysis in Cajanus cajan revealed that several K + transport genes, that is, CcHAK6 , CcHAK15 , CcAKT2 , and CcHKT1 , were up-regulated in response to drought stress [ 55 ]. Notably, the K content in the roots of P. ussuriensis was significantly higher than that of Na and Ca under PEG-induced drought stress ( Figure 9 A–C).…”
Section: Discussionmentioning
confidence: 99%
“…Some transporters, namely HvHAK1 , HvAKT2 , OsHAK1 , and OsHAK5 , have been shown to be involved in the uptake of K + in the roots [ 53 , 54 ]. Expression analysis in Cajanus cajan revealed that several K + transport genes, that is, CcHAK6 , CcHAK15 , CcAKT2 , and CcHKT1 , were up-regulated in response to drought stress [ 55 ]. Notably, the K content in the roots of P. ussuriensis was significantly higher than that of Na and Ca under PEG-induced drought stress ( Figure 9 A–C).…”
Section: Discussionmentioning
confidence: 99%
“…The conserved amino acid sequences of six KUP/HAK/KT domains are GDLGTSPLY, ANDDNGEGG, GDGVLTPAIS, GSEAMFADLGHF, AYGIAVV, and FRCIVIYGYKD, respectively. All HAK members contain at least two KUP/HAK/KT domains, which were similar to those HAKs members from Gossypium raimondii [ 28 ] and Cajanus cajan [ 29 ].…”
Section: Resultsmentioning
confidence: 71%
“…Among K + channels, the presence of ANK, Ion_trans_2, and KHA domains in the Shaker proteins, similar to Arabidopsis K + channels, suggests their functional similarities ( Keisham et al., 2018 ). Likewise, the occurrence of the significantly conserved residues, i.e., GYGD and RSXpS/pTXP, in MiTPKs indicates potential functional similarities in M. indica and other plants ( Ge et al., 2020 ; Siddique et al., 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…The current study identified 37 potential genes of the K + transport system in M. indica genome. The number of PTGs is more or less similar in major plant groups represented by V. vinifera , Glycine max , Triticum aestivum , Vigna radiata , C. cajan , and A. thaliana ( Cuéllar et al., 2010 ; Isayenkov et al., 2011 ; Chen et al., 2017 ; Azeem et al., 2018 ; Azeem et al., 2021a ; Azeem et al., 2021b ; Ge et al., 2020 ; Siddique et al., 2021 ; Cai et al., 2021 ). It not only indicates the evolutionary conservation of PTGs in these plants but also predicts the existence of similar genetic mechanisms for K + in other fruit trees.…”
Section: Discussionmentioning
confidence: 99%